Silver nanoparticles with different morphologies: growth mechanism and stability. (2nd January 2016) - Li, Kai; Wu, Qian; Xu, Tingting; Kang, Qian; Yao, Mengjuan; Song, Ge; Lin, Yuqing; Chen, Zhengbo; Zheng, Tingting
Abstract : Silver nanoparticles (Ag NPs) with different morphologies, including spherical, hexagonal, triangular and wirelike shapes, were prepared by chemical reduction method. The obtained Ag NPs were characterized by transmission electron microscopy (TEM), high-resolution TEM (HRTEM), energy dispersive spectroscopy (EDS), field emission scanning electron microscopy (FE-SEM), UV–vis spectrophotometer and X-ray diffractometer. The results showed that Ag nanospheres, hexagonal Ag nanoplates, triangular Ag nanoplates and Ag nanowires were prepared using different reducing agents and capping agents. The growth mechanisms of Ag NPs were proposed. Ostwald ripening was the driving force for the shape evolution from spherical Ag NPs into unisotropic Ag NPs. In addition, the stability of triangular Ag nanoplates and Ag nanowires were firstly investigated.